PHYTOCHEMICAL SCREENING, TOXICITY AND ANTI-BACTERIAL ASSAY FROM STEM-BARK EXTRACTS OF Garcinia celebica and G. tetandra - Yuliasri Jamal; Praptiwi .; Andria Agusta (Indonesian Journal of Pharmacy, 2001)
Garcinia is suggested to have multi benefit in curing various diseases, some have edible fruit and edible oil. This experiment was a preliminary analysis, including phytochemistry screening, toxicity and antibacterial testing of stem-bark G. celebica and G. tetandra extracts. Ether, ethanol and water extracts of both Garcinia contained 19 different chemical components. Hexane, methanol and water extracts of stem-bark of both Garcinia extracts were found to have toxicological effect on Artemisia salina larva, G. celebica water extract had highest LC50 . Dichloromethane-methanol 1:1 extract of G. celebica inhibited the growth of Gram positive and Gram negative bacteria , while the extract of G. tetandra could only inhibit the growth of Gram negative bacterium. Comparing with erythromycin and novobiosin antibiotics, the inhibiton growth activity of the two Garcinia extracts were lower than those of the antibiotics. Key words: Garcinia, phytochemical screening, toxicological effect, anti-bactery